Productivity and nutritional quality of forage sorghum cultivars used in northeastern Argentina - Loizaga, Ulises Daniel; Cajide, Ernesto Javier; Chabbal, Marco Daniel; Giménez, Laura I.; Botta, Guido Fernando; Hidalgo, Ramón Jesús (Ediciones INTA, 2025)
The objective of the work reported in this paper was to evaluate the productivity and nutritional quality of ten sorghum cultivars in the northeastern region of Argentina, with and without the application of basic fertilizers. The types studied were the following: fodder sorghum, dual-purpose, biomass sorghum (silage sorghum), sudan grass (Sorghum × drummondii (Steud.) Millsp. & Chase) and multipurpose sorghum. A split-plot design was carried out considering these factors: cultivar, fertilization and the interaction of both. The evaluated cultivars presented differences in productivity and quality. Two dual-purpose cultivars, one silage and one multipurpose, showed the highest potential for green and dry matter accumulation. However, the last two presented a lower energy contribution, mainly due to their large proportion of acid detergent fiber (ADF). The application of basic phosphorus and nitrogen fertilizer was favorable for the development of the crop, observing differences in yield up to 5,000 kg ha-1 of dry matter in the means of the treatments. Among all the fodder sorghum cultivars studied, the fertilized BMR (Brown Middle Rib) 500 Peman cultivar presented the highest digestibility values, although it showed the lowest yield. Finally, it should be point out that, to select a genotype in a specific productive approach, all the productive and nutritional quality variables must be analyzed together.